La diabetes como factor desencadenante de los estados depresivos y su incidencia en la calidad de vida de los pacientes ambulatorios del hospital San Vicente de Paul del cantón Pasaje, periodo 2014-2015. - Cabanilla Espinoza, Lisseth Estefanía (2015)
This research is very important in our society due to increased diabetics in Canton Pasaje El Oro Province, the problems that are causing serious disturbances on the mental health of people with diabetes.